Combining RADseq and contact zone analysis to decipher cryptic diversification in reptiles: Insights from the Spiny‐footed Lizard (Reptilia, Lacertidae) - Doniol‐Valcroze, Paul; Rancilhac, Loïs; Brito, José‐Carlos; Miralles, Aurélien; Geniez, Philippe; Benoit, Laure; Loiseau, Anne; Leblois, Raphaël; Dufresnes, Christophe; Crochet, Pierre‐André (Zoologica scripta, 2024)
Uncertainties on species taxonomy and distribution are major factors hampering efficient conservation planning in the current context of biodiversity erosion, even concerning widespread and abundant species in relatively well‐studied regions. Species delimitation have long been based on phylogenetic analyses of a small number of standard markers, but accurate lineage identification through this approach can be hampered by incomplete lineage sorting, introgression or isolation by distance. In that context, analyses of introgression patterns at secondary contact zones offer an interesting alternative by allowing a direct estimation of reproductive isolation, especially when using genome‐wide markers. Here, we investigated a contact zone between two genetic groups of the Spiny‐footed Lizard Acanthodactylus erythrurus (Schinz, 1833) in Morocco, whose status as separate lineages remained disputed in previous multilocus studies. Based on thousands of genome‐wide markers obtained through a RADseq approach, we confirmed that they represent distinct evolutionary lineages. Furthermore, the transition at their contact zone was very steep, with spatially restricted gene flow, highlighting levels of reproductive isolation consistent with species‐level lineages. Our study further illustrates the power of RADseq‐based studies of contact zones to understand cryptic diversity in non‐model organisms.